Broadband THz absorption using nanosheets of Bi2Te3 grown on a transparent conductor. Issue 4 (9th January 2023) - Pandey, Animesh; Banerjee, Sabyasachi; Yadav, Reena; Kumar, Sumit; Jewariya, Mukesh; Chowdhury, Dibakar Roy; Lalla, N. P.; Husale, Sudhir
Abstract : Demonstration of broadband THz absorber based nanostructures of topological insulators. Abstract : When contrasted to their bulk counterparts, nanostructures exhibit quantum confinement effects, resulting in exotic optical characteristics. Here we employed a straightforward one-step confined thin-film melting technique to synthesize Bi2 Te3 nanosheets on a transparent conductor (TC) without the use of a conventional template and catalyst. The Bi2 Te3 nanosheets have been investigated using Raman, SEM, AFM, and TEM to confirm that the synthesized nanosheets exhibit a single crystalline quality. THz-time-domain spectroscopy in transmission mode is used to investigate the properties of Bi2 Te3 nanosheets grown on a TC substrate by this method which shows a remarkable broadband absorption between 0.1 to 4.0 THz. This indicates that our work shows a considerable possibility that such large area Bi2 Te3 nanosheets grown on a TC can be used as THz absorbers in fields like terahertz electromagnetic stealth, communications and optoelectronics industries.